Digit ratio (2D:4D) and competition level in world-class female gymnasts - Peeters, M. W.; Claessens, A. L. (Journal of Sports Sciences, 2013)
In this study the relationship between the digit ratio (2D:4D) and artistic gymnastics performance and competition level was investigated in a sample of Caucasian world-class female gymnasts (n = 145). The sample was divided into three competition events (compulsories, free work, final score). Within each event three performance groups (lowest, middle, and highest) were based on the competition scores gathered at the World Championships at Rotterdam, the Netherlands, in 1987. Lengths of the digits were measured on X-rays of the left hand. Several anthropometric dimensions were measured and from those measurements an androgyny index (Bayer & Bayley) and somatotype components (endomorphy, mesomorphy, ectomorphy) were calculated. Although significant differences in some anthropometric characteristics between the performance level groups within each competition event were observed, no significant differences in the 2D:4D ratios were found between the performance level groups, varying from 0.918 ± 0.020 to 0.924 ± 0.020. Also, no significant correlations were observed between the 2D:4D ratio and anthropometric, androgyny, and somatotype characteristics, r varying from r = -0.11 to r = +0.12. It can be concluded that in this sample the 2D:4D digit ratio, unlike other anthropometric characteristics, is not a discriminating factor for the performance in artistic gymnastics performance on a world-class level.